Konflik Identitas Perempuan dalam Novel Tutur Dedes Doa dan Kutukan Karya Amelia Yunus : The conflict of women's identities in the novel Dedes, Prayers and Curses by Amelia Yunus - ‘Aini, Tamara Qurrotul; Sutejo, Sutejo; Latifah, Suci Ayu (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Women's identity conflict is a situation where women experience confusion, doubt, or uncertainty about their identity as women. The aim of this research is to find out how women's identities conflict in the novel Tutur Dedes Doa dan Kutukan by Amelia Yunus. In this research, the method used is qualitative, and uses the conflict theory of Simon Fisher and Deka Ibrahim et al. The data collection techniques used were written and library sources, while the data analysis used included classifying data, reviewing/analyzing data and describing data. The object used is a novel entitled Tutur Dedes Prayers and Curses by Amelia Yunus. Based on the analysis, the researchers found five conflicts, including individual differences, cultural differences, differences in interests, social change, and finally political change. It can be concluded that the identity conflicts that are often found in women are identity conflicts due to individual differences and political changes.